Strategi Komunikasi Pondok Pesantren dalam Menyosialisasikan Moderasi Beragama: Persepsi Masyarakat Aceh Singkil terhadap Upaya Deradikalisasi - Sarkawi; Hasan Sazali (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
As a religious country, Indonesia recognizes 6 (six) religions and provides the right and equal position in the law to carry out their respective beliefs, Besides that, Indonesia which adheres to Bhinneka Tunggal Ika is not all understood by the community in all aspects, so that there is a potential for conflict or conflict. understood by the community in all aspects, so that the potential for conflict or grouping each other into a problem in grouping each other into a problem in the territory of a unitary state, for this reason, religious moderation activities that are promoted by the government become an important activity and even this activity is also carried out by the government. important activities and even this activity is also carried out in the Islamic boarding school by displaying various traditions from Christianity. by displaying various traditions from Christianity. Research with the Title Socialization of religious moderation in Islamic boarding schools in the view of the Aceh Singkil community. Aceh Singkil is a qualitative research, aims to find out how the community views the Religious Moderation Socialization activities socialization activities carried out in Islamic boarding schools, which in fact have been understood as the center of Islamic studies. as the center of Islamic studies. From the results of the research conducted at least can be conclusions can be drawn (1) Religious Moderation Socialization activities are good activities to unite the Indonesian nation (2) Religious Moderation Socialization activities carried out in the Indonesian nation (2) Religious Moderation Socialization activities in Islamic boarding schools are not a problem because they support the policies of the Islamic Boarding School. Pesantren is not a problem because it supports Government Policy (3) Appearances and Cultures that violate Islamic Sharia and Special Traditions for other religions are seen as less beautiful in the Islamic Boarding School. Other religions are considered less Appropriate to be displayed in Islamic Boarding Schools.